ANALISIS KONTRIBUSI PRAKTIK KERJA LAPANGAN TERHADAP KOMPETENSI SISWA JURUSAN TEKNIK AUDIO VIDEO DI SMK NEGERI 1 ENREKANG - Selvitasari; ., Purnamawati; Sidik, Darlan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Field Work Practice (FWP) is an essential component of vocational education that provides students with practical experience aligned with industry needs. This study aimed to analyze the implementation of Field Work Practice, examine students' competence after participating in the program, and determine the contribution of Field Work Practice to the competence of Audio Video Engineering students at SMK Negeri 1 Enrekang. This research employed a quantitative approach using an associative survey design. The population consisted of 35 twelfth-grade students who had completed Field Work Practice, and all were selected as the sample through total sampling. Data were collected using a Likert-scale questionnaire and analyzed through descriptive statistics and simple linear regression with SPSS. The results revealed that Field Work Practice had a positive and significant contribution to students' competence. The correlation coefficient (R) was 0.767, indicating a strong relationship, while the coefficient of determination (R²) was 0.588, meaning that Field Work Practice contributed 58.8% to students' competence. Hypothesis testing showed a significance value below 0.05 and a t-value of 6.867, confirming that the alternative hypothesis was accepted. Therefore, improving the quality of Field Work Practice is expected to enhance students' competence in vocational education.